2021
DOI: 10.1051/e3sconf/202126302052
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of concrete beams reinforced with FRP during bending

Abstract: Article describes methods and results of experimental research for strain behavior, crack formation and fracture of concrete beams reinforced with fiber reinforced polymer (FRP) bars during bending moment action. 18 beams (3+3 series) reinforced with glass FRP (GFRP) and basalt (BFRP) 6, 10 and 14 mm in diameter were tested. Deflection in the middle of the beam, concrete and bars strain and ultrasonic transmission time for 4 routes were measured during tests besides visual inspection. Main crack formation occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This research has shown that failures in strengthened RC beams are obtained after large deflections and steel rebars yielding with FRP debonding. This debond can occur in the concrete part of the beam through intermediate debonding or through peeling-off at the end of the plate [18].…”
Section: Introductionmentioning
confidence: 99%
“…This research has shown that failures in strengthened RC beams are obtained after large deflections and steel rebars yielding with FRP debonding. This debond can occur in the concrete part of the beam through intermediate debonding or through peeling-off at the end of the plate [18].…”
Section: Introductionmentioning
confidence: 99%